Design Of High-Altitude Falling Object Alert System - Dong, Xinyue (International Journal of Computer Science and Information Technology, 2024)
As urbanization accelerates, the number of high-rise buildings in cities has increased significantly, leading to frequent incidents of objects falling from great heights. These incidents pose a serious threat to public safety and property. This paper describes the design and implementation of a real-time monitoring and alert system for high-altitude falling objects aimed at enhancing urban safety management efficiency and effectiveness. This paper describes the design and implementation of a real-time monitoring and alert system for high-altitude falling objects aimed at enhancing urban safety management efficiency and effectiveness. The system employs an STM32 controller to monitor and alert the falling objects. system employs an STM32F103C8T6 microcontroller as its core processor, coupled with two infrared sensors and an ESP32-CAM camera for detection purposes. It assesses the presence of falling objects by analyzing signals from these sensors and alerts pedestrians through LED indicators and buzzers. It assesses the presence of falling objects by analyzing signals from these sensors and alerts pedestrians through LED indicators and buzzers. Additionally, it includes a mobile app for remote monitoring, enabling users to check conditions and respond promptly. The system’s design and accuracy were further validated through simulation experiments conducted with Python, which confirmed that the alert system reliably detects falling incidents and promptly issues warnings, thereby reducing the number of pedestrians and alerts pedestrians through LED indicators and buzzers. The system’s design and accuracy were further validated through simulation experiments conducted with Python, which confirmed that the alert system reliably detects falling incidents and promptly issues warnings, thereby significantly improving safety measures.